The Effects of Mixed Robinia pseudoacacia and Quercus variabilis Plantation on Soil Bacterial Community Structure and Nitrogen-Cycling Gene Abundance in the Southern Taihang Mountain Foothills - Yi Yang; Jing Chen; Yiwei Zheng; Rui Jiang; Yuqiang Sang; Jinsong Zhang (Microorganisms)
Mixed forests often increase their stability and species richness in comparison to pure stands. However, a comprehensive understanding of the effects of mixed forests on soil properties, bacterial community diversity, and soil nitrogen cycling remains elusive. This study investigated soil samples from pure Robinia pseudoacacia stands, pure Quercus variabilis stands, and mixed stands of both species in the southern foothills of the Taihang Mountains. Utilizing high-throughput sequencing and real-time fluorescence quantitative PCR, this study analyzed the bacterial community structure and the abundance of nitrogen-cycling functional genes within soils from different stands. The results demonstrated that Proteobacteria, Acidobacteria, and Actinobacteria were the dominant bacterial groups across all three forest soil types. The mixed-forest soil exhibited a higher relative abundance of Firmicutes and Bacteroidetes, while Nitrospirae and Crenarchaeota were most abundant in the pure R. pseudoacacia stand soils. Employing FAPROTAX for predictive bacterial function analysis in various soil layers, this study found that nitrogen-cycling processes such as nitrification and denitrification were most prominent in pure R. pseudoacacia soils. Whether in surface or deeper soil layers, the abundance of AOB amoA, nirS, and nirK genes was typically highest in pure R. pseudoacacia stand soils. In conclusion, the mixed forest of R. pseudoacacia and Q. variabilis can moderate the intensity of nitrification and denitrification processes, consequently reducing soil nitrogen loss.